Network Pharmacology and Data Mining Approach Reveal the Medication Rule of Traditional Chinese Medicine in the Treatment of Premenstrual Syndrome/Premenstrual Dysphoric Disorder - Qu, Songlin; Qiao, Mingqi; Wang, Jieqiong; Gao, Mingzhou; Chen, Dan; Li, Shujing; Wei, Enhua; Guo, Yinghui (Frontiers in Pharmacology, 2022)
Premenstrual Syndrome(PMS) is a common disorder that affects women of reproductive age. It is characterized by periodic mental and somatic symptoms such as irritability, depression, and breast pain during the luteal phase. Premenstrual Dysphoric Disorder (PMDD) is the most severe form of the PMS. In recent years, the incidence of PMS/PMDD has increased year after year, however, due to the complex symptoms and ambiguous classification of PMS/PMDD, the limitations of present treatments such as their poor efficacy rate, have become increasingly apparent. With its unique benefits such as syndrome differentiation and high cure rate. Traditional Chinese medicine (TCM) has sparked new concepts for the diagnosis and treatment of PMS/PMDD. This article uses data mining methods and statistical analysis revealed that Xiaoyao San and Chaihu Shugan San were some of the commonly used TCM for the treatment of PMS/PMDD. A detailed investigation of regularly used single herbs revealed that the majority of TCM is used as cold drugs that penetrate the liver meridian, with predominant bitter, sweet, and pungent flavors. Through network pharmacology method to analyse the interactions between diseases, genes, targets and drugs. Meanwhile, the deep action targets and molecular mechanisms of 10 commonly used Chinese medicines for the treatment of PMS/PMDD are studied, revealing that it involves several substances, many targets, and different pathways, this interaction provides insight into the mechanism of action of traditional Chinese medicine in the synergistic treatment of PMS/PMD. It is now clear that we can attempt to begin treating PMS/PMDD with TCM using the target and mechanism revealed by the above findings in the future. This serves as an important reference for future research and clinical application of TCM in the treatment of PMS/PMDD.